Fundamental of Entrepreneurship ENT300 : Big Show & Co Cinema / Murvyn Chundi Michael ... [et al.] - Michael, Murvyn Chundi; Jamel, Muhammad Aiman; Abdul Hamid, Mohd Noor Fariswan; Winston, Charleston Lambong; Gerinang, Andrian Nasir (2014)
This business is based on partnership where it consists of five (5) members. The members consist of the General Manager, Marketing Manager, Operation Manager, Administrative Manager and Financial Manager. The business capital is amounted to RM 315,000 where the total contribution of each member is RM 35,000 and the rest is from the CIMB Bank Bhd loan.BIG SHOW & CO CINEMA is a company related to movie screening or cinema. Our market focus is for teenagers and family around Kuching. Our business will be expected to commence on 2015 and our vision is to create a harmonious, productive, profitable yet new cinema environment. Also, our vision is to be a trademark in Kuching, where people would think of "The Big Show" the famous open-air cinema in town, whenever they heard of Kuching. This will be realized by the full cooperation and efforts among the partners to promote this company.